Expert systems and robotics - NATO Advanced Study Institute on Expert Systems and Robotics (1990 : Kerkyra, Greece); Jordanides, Timothy; Torby, Bruce J.; North Atlantic Treaty Organization. Scientific Affairs Division (Berlin : Springer-Verlag, 1991)
20